Proceedings of the 7th International Conference on ICT for Sustainability 2020
DOI: 10.1145/3401335.3401619
|View full text |Cite
|
Sign up to set email alerts
|

Towards a conceptual framework of direct and indirect environmental effects of co-working

Abstract: Through virtual presence, information and communication technology (ICT) allows employees to work from places other than their employer's office and reduce commuting-related environmental effects (telecommuting). Working from a local co-working space, as a form of telecommuting, has the potential to significantly reduce commuting and is not associated with deficits of working from home (e.g. isolation, lack of focus). However, environmental burden might increase through co-working due to the infrastructure req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Similar conclusions are reached by Bieser et al [69], analyzing how the co-working practice impacted the time use of employees in Stockholm via the time use diary approach. Together with Vaddadi et al [70], they discovered that it could lead to a substitution effect concerning the transport mode, as co-working spaces are usually located in the neighborhood of the households, providing an incentive to use bikes, public transport or walking instead of traveling by private cars.…”
Section: The Case Of Teleworkingmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar conclusions are reached by Bieser et al [69], analyzing how the co-working practice impacted the time use of employees in Stockholm via the time use diary approach. Together with Vaddadi et al [70], they discovered that it could lead to a substitution effect concerning the transport mode, as co-working spaces are usually located in the neighborhood of the households, providing an incentive to use bikes, public transport or walking instead of traveling by private cars.…”
Section: The Case Of Teleworkingmentioning
confidence: 99%
“…Twelve papers analyzed the energy implications of behavioral changes due to teleworking, with eight studies adopting analytical models to quantify them [61], [34,73], [69,70,72,74,76]. The energy savings obtained by less commuting are considered in all of them.…”
Section: The Case Of Teleworkingmentioning
confidence: 99%
See 2 more Smart Citations
“…Many further studies on the GHG abatement potential of ICT can be found in the literature, e.g. [31][32][33][34][35][36][37][38][39][40], for an overview see [41]. Some technology providers and consulting companies have already investigated indirect effects of 5G on GHG emission in other countries [42,43]; however, we could not find a study published by the scientific community.…”
Section: Introductionmentioning
confidence: 99%